Strategi Kepala Sekolah dalam Meningkatkan Mutu Pendidikan di Madrasah Aliyah - M. Haikal Fadhil; Riduwan Riduwan; Hasyim Asyari; Maftuhah Maftuhah; Zahruddin Zahruddin (STIKes Ibnu Sina Ajibarang, 2025)
Improving the quality of education in Madrasah Aliyah (MA) is one of the major challenges in the Indonesian education system, which combines religious and general curriculum. The purpose of this study is to describe and analyze 1) planning, 2) implementation, 3) evaluation, and 4) obstacles to the principal's strategy in improving the quality of education at MA Da'il Khairaat West Jakarta. The research method used is descriptive qualitative. The data source in this study is primary data, namely the Principal, while the secondary data of this study are the Deputy Head of Academic Affairs, Deputy Head of Student Affairs, Deputy Head of Religious Affairs, Teachers, Committee, Students, and Parents. Data collection methods are by observation, interviews, and documentation. The validity test of the data uses triangulation techniques, sources and extension of observations. While data analysis with an interactive model begins with data collection, reduction, presentation, and drawing conclusions. The results of the study of the principal's strategy in improving the quality of education are 1) Strategic planning begins with an analysis of the internal and external environment, 2) Implementation of the principal's strategy, namely the division of job descriptions; 3) Evaluation of the principal's strategy, namely direct supervision of the program's implementation, 4) obstacles and solutions to the principal's strategy in improving quality, namely the first obstacle is human error, the principal's solution is to provide coaching, the second is the lack of facilities and infrastructure, the solution is to add facilities and infrastructure by working together with parents.